Nationalism Among Students: A Comparison Between Students of Islamic Junior High School and Students Of Junior High School in Serang Municipality and Serang Regency - Fauzi, Anis (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This article aims to explore the nationalism among students Islamic Junior High School (MTs) and Junior High School (SMP) in the District of Serang and Serang Municipality. Statistical analysis show that in order to find a comparison between the national insight MTs and SMP students Â in research location by using Test t to sample a large group. Based this study, it is concluded that there was no significant difference between the nationalistic viewpoint MTs and SMP students in Serang Municipality withÂ MTs Â and SMP students in Serang District. However, basing on the difference between the average value the mean between the two groups of respondents turned out to mean price MTs and SMP student groups in Serang City (204.235) were slightly larger than the mean price of MTs and SMP school student groups in the district of Serang (203.765).—–Artikel ini bertujuan untuk mengeksplorasi wawasan kebangsaan siswa Madrasah Tsanawiyah (MTs) dan Sekolah Menengah Pertama (SMP) di wilayah Kabupaten Serang dan Kota Serang. Kemudian melakukan analisis statistik dalam rangka mencari perbandingan wawasan kebangsaan antara siswa MTs dan SMP di lokasi penelitian dengan menggunakan Tes âtâ untuk sampel kelompok besar. Dalam studi ini disimpulkan bahwa tidak terdapat perbedaan yang signifikan antara wawasan kebangsaan siswa MTs dan SMP di Kota Serang dengan Siswa MTs dan SMP Kabupaten Serang. Namun demikian, berdasarkan selisih nilai rata-rata (mean) antar kedua kelompok responden ternyata harga mean kelompok siswa MTs dan SMP di Kota Serang (204,235) sedikit lebih besar dibandingkan dengan mean kelompok siswa MTs dan SMP di Kabupaten Serang (203,765).Â